Dengue virus-like particles mimic the antigenic properties of the infectious dengue virus envelope - Stefan W. Metz (Virology Journal, 2018)
Abstract Background The 4 dengue serotypes (DENV) are mosquito-borne pathogens that are associated with severe hemorrhagic disease. DENV particles have a lipid bilayer envelope that anchors two membrane glycoproteins prM and E. Two E-protein monomers form head-to-tail homodimers and three E-dimers align to form “rafts” that cover the viral surface. Some human antibodies that strongly neutralize DENV bind to quaternary structure epitopes displayed on E protein dimers or higher order structures forming the infectious virus. Expression of prM and E in cell culture leads to the formation of DENV virus-like particles (VLPs) which are smaller than wildtype virus particles and replication defective due to the absence of a viral genome. There is no data available that describes the antigenic landscape on the surface of flavivirus VLPs in comparison to the better studied infectious virion. Methods A large panel of well characterized antibodies that recognize epitope of ranging complexity were used in biochemical analytics to obtain a comparative antigenic surface view of VLPs in respect to virus particles. DENV patient serum depletions were performed the show the potential of VLPs in serological diagnostics. Results VLPs were confirmed to be heterogeneous in size morphology and maturation state. Yet, we show that many highly conformational and quaternary structure-dependent antibody epitopes found on virus particles are efficiently displayed on DENV1–4 VLP surfaces as well. Additionally, DENV VLPs can efficiently be used as antigens to deplete DENV patient sera from serotype specific antibody populations. Conclusions This study aids in further understanding epitopic landscape of DENV VLPs and presents a comparative antigenic surface view of VLPs in respect to virus particles. We propose the use VLPs as a safe and practical alternative to infectious virus as a vaccine and diagnostic antigen.